The civilized organization : Norbert Elias and the future of organization studies - Iterson, Ad van, 1952- (Advances in organization studies, 2002)
This book brings a major new resource to organization studies: the work of Norbert Elias. By applying his ideas in a critical but sympathetic way, the authors provide a new perspective on the never-ending stream of management fads and fashions. Standing back and taking a more detached perspective, inspired by the work of Norbert Elias (1897-1990), it becomes clear that many 'new' types of organizations are often variations on an old theme. Elias gives us considerable purchase on current debates through his emphasis on long-term historical perspectives, his highlighting of issues of power, emoti.